2016
DOI: 10.5539/jfr.v5n2p73
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Starch Hydrolysis and Prediction of Glycemic Index (PGI) in “Amala” and Plantain Based Baked Products

Abstract: Various levels of bambara groundnut protein cocnentrate ranging from 0 to 15% were used in the formulation of plantain paste (Amala) and plantain baked products. 'Amala' and cookies were produced from 85% plantain flour and 15% bamabara groundnut protein concentrate, while cakes and bread were produced from 70% wheat flour, 20% plantain flour and 10% bambara groundnut protein concentrate. Starch fractions and in vitro starch hydrolysis of the products were determined. The lowest total starch value was found in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 29 publications
(28 reference statements)
0
12
0
Order By: Relevance
“…Dietary fiber, as the indigestible portion of food, is resistant to digestion and absorption in gastrointestinal tract (Otles and Ozgoz 2014). Previous works have shown that highfibre food led to the lower starch hydrolysis in vitro (Leoro et al, 2010;David Barine and Yorte 2016), therefore, it is expected that the incorporation of olive pomace may reduce the starch digestibility and consequently expected GI in vitro. As shown in Fig.…”
Section: Starch Digestibility Of Olive Pomace Incorporated Biscuitmentioning
confidence: 99%
“…Dietary fiber, as the indigestible portion of food, is resistant to digestion and absorption in gastrointestinal tract (Otles and Ozgoz 2014). Previous works have shown that highfibre food led to the lower starch hydrolysis in vitro (Leoro et al, 2010;David Barine and Yorte 2016), therefore, it is expected that the incorporation of olive pomace may reduce the starch digestibility and consequently expected GI in vitro. As shown in Fig.…”
Section: Starch Digestibility Of Olive Pomace Incorporated Biscuitmentioning
confidence: 99%
“…Though the GI values obtained from the standard Englyst method stayed closer to the developed in‐vitro method (Table 2), the k values seemed to remain higher. These higher values obtained from Englyst method showed an increased susceptibility to enzymatic hydrolysis when compared to the modified in‐vitro method (David Barine & Yorte, 2016). This may be due to the use of dialysis membrane in the developed method, which only measures the diffused glucose concentration.…”
Section: Resultsmentioning
confidence: 90%
“…Total, resistant and digestible starch analysis Two hundred milligrams of test and control crackers were tested in accordance with previously established procedures (Siddhuraju, & Becker, 2005;Barine, & Yorte, 2016), with modifications as previously reported (Njume et al, 2020). A standard solution of glucose (20, 40, 60, 80 and 100 mg/L) was prepared for the generation of a standard curve (plotting absorbance at 630 nm against concentration mg/mL, r-value = 0.999).…”
Section: Plant Component Analysis By Reverse-phase Highperformance Liquid Chromatography (Rp-hplc)mentioning
confidence: 99%
“…The sample glucose concentration was obtained from the standard curve. The experiment was repeated twice, and the glucose measurements converted to starch by multiplying the percentage glucose concentration by 0.9 (Barine, & Yorte, 2016). For determination of resistant starch (RS), 100 mg of the residue from the total starch analysis was tested as previously reported (Siddhuraju, & Becker, 2005;Barine, & Yorte, 2016).…”
Section: Plant Component Analysis By Reverse-phase Highperformance Liquid Chromatography (Rp-hplc)mentioning
confidence: 99%
See 1 more Smart Citation